DEVELOPMENT OF E-MODULES BASED ON FLIPBOOKS WITH VARIOUS OCCUPATION THEMES FOR CLASS IV STUDENTS - QIFTIYAH, MARATUL (Universitas Nahdlatul Ulama Pasuruan, 2024)
This research aims to find out how to develop flipbook-based thematic learning e-modules, determine the feasibility of flipbook-based thematic learning e-modules, and find out the response of educators and students to the use of flipbook-based thematic learning e-modules. This research is a type of research and development using the ADDIE model. Based on the analysis of the needs of educators and students, it was concluded that students need the e-learning modules that researchers have developed. Flipbook-based thematic learning e-modules are validated by media experts and material experts. Thematic learning e-modules were tested on 25 class IV students at SDN Cepoko. Thematic learning e-modules are produced through stages, namely analysis, design, development, implementation, and evaluation. The results of validation by material experts were carried out twice, obtaining an overall score of 90% with the criteria